2016
DOI: 10.21162/pakjas/16.3341
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Mitigating the Impacts of Drought Stress in Cotton- A Review

Abstract: Water scarcity is the most serious abiotic stress restricting plant productivity throughout the world. Losses in crop yield due to drought exceed from losses caused by other environmental factors. In this review article different morphological, physiological and yield attributes of cotton under drought stress, mechanism of drought induced losses and various management strategies to mitigate drought stress have been discussed. Drought stress reduces growth of leaf, stem and root, interferes with leaf water rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 120 publications
1
19
1
Order By: Relevance
“…Researchers showed that the higher leaf turgor potential resulted in the accumulation of osmotic materials such as total sugar content (Ali and Radwan, 2008;Chutia and Borah, 2012;Saleem et al, 2016;Raza et al, 2017). We also found that the contents of total sugar and proline significantly increased under PRD irrigation (Figs.…”
Section: Prd Affecting the Biochemical Traits Of Cottonsupporting
confidence: 54%
See 1 more Smart Citation
“…Researchers showed that the higher leaf turgor potential resulted in the accumulation of osmotic materials such as total sugar content (Ali and Radwan, 2008;Chutia and Borah, 2012;Saleem et al, 2016;Raza et al, 2017). We also found that the contents of total sugar and proline significantly increased under PRD irrigation (Figs.…”
Section: Prd Affecting the Biochemical Traits Of Cottonsupporting
confidence: 54%
“…Previous studies revealed that activities of these enzymes significantly increased under PRD irrigation (Javanovic and Stikic, 2018), thus reducing the harmful effects of drought in cotton (Ullah et al, 2017). Similarly, mulching maintains the water balance (osmotic and turgor potentials) that is necessary for normal cotton growth (Saleem et al, 2016). As the application of PRD or mulching is favorable for counteracting drought so their combination should be investigated to estimate the extent of drought mitigation in cotton.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton is an important textile fiber and oil seed crop [ 33 ]; however, the repercussions of climate change, particularly drought stress, are severely limiting its production globally [ 34 ]. Our laboratory previously released Gossypium arboreum sequencing data [ 35 ] and RNA-seq studies have revealed hormone crosstalk, whereby MYB TFs are implicated in modifying plant responses toward drought and NaCl stresses in different tissues [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stress triggered the degradation of chlorophyll which ultimately decreased carbon availability for biosynthesis of antioxidants in cotton. Early senescence also downregulated synthesis of osmoprotectants and thereby disrupted water relations under stress environment (Saleem et al 2016;Saleem et al 2018c). Disturbances in water relations caused by chlorophyll degradation were related to inhibition of ribulose-1,5-bisphosphate carboxylase activities in cotton under stress conditions (Zahoor et al 2017).…”
Section: •-mentioning
confidence: 99%